Epidemiology of tick-borne diseases - Lyme disease and nodular Scar Fever - epidemiological data from the years 2012 and 2021 in the Regional Health Administration of Lisbon and Tagus Valley - Rosa, Marta Maria Gonçalves; Amaro, Sandra Maria Fernandes Ribeiro; Monterroso, Lígia Eduarda Pereira (Seven Editora, 2024)
Diseases transmitted by ticks constitute a problem within the scope of community health and public health. Over the years, national authorities have been making efforts to reduce these diseases, increasing the literacy of the Portuguese population regarding this problem. Diseases transmitted by these vectors have been appearing or reappearing in the national territory, because of different climatic, demographic, and social changes, associated with genetic changes in the vectors themselves. Therefore, we developed a literature review in several available computer sources and physical collections, supported by epidemiological and biostatistical data at national level (Portugal), in the years 2012-2021, focusing on the region of the Regional Administration of Lisbon and Vale do Tejo, for convenience. of researchers. Therefore, we intend to alert and sensitize the academic and care provider community to the need to be aware and respond to specific norms and indications regarding the approach of users, implementing nursing interventions based on national strategies and guidelines, to raise awareness among the population, hoping that in the future the number of diseases transmitted by ticks would decrease. DOI:https://doi.org/10.56238/sevened2023.006-132